Practical compassions: repertoires of practice and compassion talk in acute mental healthcare - Brown, Brian; Crawford, Paul; Gilbert, Paul; Gilbert, Jean; Gale, Corinne (Wiley, 2014)
This article reports an exploratory study of the concept of compassion in the work of 20 mental health practitioners in a UK Midlands facility. Using notions of practice derived from phenomenology and Bourdieusian sociology and notions of emotional labour we identify two contrasting interpretive repertoires in discussions of compassion. The first, the practical compassion repertoire, evokes the practical, physical and bodily aspects of compassion. It involves organising being with patients, playing games, anticipating disruption and taking them outside for cigarettes. Practitioners described being aware that these practical, bodily activities could lead to patients ‘opening up’, disclosing their interior concerns and enabling practical, compassionate mental health work to take place. In contrast, the second, organisational repertoire, concerns organisational constraints on compassionate practice. The shortage of staff, the record-keeping and internal processes of quality control were seen as time-greedy and apt to detract from contact with patients. The findings are discussed in relation to Bourdieu and Merleau-Ponty's phenomenological accounts of practice and habit and set in context in the growing interest in placing compassion centrally in healthcare. We also explore how the exercise of compassion in the way our participants describe it can afford the more effective exercise of medical power.